Kajian Aspek Fotografis dalam Tehnik Olah Digital Poster Film “ Sang Pemimpi ” - CM, Noor Latif (Humaniora, 2011)
As the advancement of digital imaging technology, this urges internal actors to be more accurate and explorative in producing visual communication work with photography element and digital touching process. Digital process ability with no photographical ability will produce raw and anomaly visual work of art. Besides, audience is smarter and more appreciative towards quality of visual appearance in several modern communication media. Film poster of Sang Pemimpi is a case reflection of general digital in visual communication work that has gap among communication product content according to the brand of the film. Photography element composition is melted with bondless pile among the objects. Logical photography as bonding bridge of visual logic is weak in execution; where we could see it has less digital process commercial market need with the supporting resources.